2021
DOI: 10.1007/s00440-021-01051-7
|View full text |Cite
|
Sign up to set email alerts
|

Critical Brownian multiplicative chaos

Abstract: Brownian multiplicative chaos measures, introduced in Jego (Ann Probab 48:1597–1643, 2020), Aïdékon et al. (Ann Probab 48(4):1785–1825, 2020) and Bass et al. (Ann Probab 22:566–625, 1994), are random Borel measures that can be formally defined by exponentiating $$\gamma $$ γ times the square root of the local times of planar Brownian motion. So far, only the subcritical measures where the parameter $$\gamma $$ γ is less than 2 were studied. This art… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…By now, Gaussian multiplicative chaos is a fundamental object in its own right which describes scaling limits arising naturally in many different contexts, including random matrices [11,25,37,49,66], the Riemann zeta function [56] and stochastic volatility models in finance [6] (see also [20]); see the surveys [50,53] and the book in preparation [10] for more context and references. More recently, it has been shown that an analogous theory can be developed in the case where ℎ describes (at least formally) the square root of the local time (that is, occupation field) of a Brownian trajectory; see [2,7,29,30,32]. The construction of the associated multiplicative chaos, a measure which we will denote in the following by  ℘ and which is now termed Brownian multiplicative chaos (following the terminology of [30]), is one of the first examples (together with [33] which studies random Fourier series with independent and identically distributed coefficients) of a multiplicative chaos in which the field ℎ is not Gaussian or approximately Gaussian.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By now, Gaussian multiplicative chaos is a fundamental object in its own right which describes scaling limits arising naturally in many different contexts, including random matrices [11,25,37,49,66], the Riemann zeta function [56] and stochastic volatility models in finance [6] (see also [20]); see the surveys [50,53] and the book in preparation [10] for more context and references. More recently, it has been shown that an analogous theory can be developed in the case where ℎ describes (at least formally) the square root of the local time (that is, occupation field) of a Brownian trajectory; see [2,7,29,30,32]. The construction of the associated multiplicative chaos, a measure which we will denote in the following by  ℘ and which is now termed Brownian multiplicative chaos (following the terminology of [30]), is one of the first examples (together with [33] which studies random Fourier series with independent and identically distributed coefficients) of a multiplicative chaos in which the field ℎ is not Gaussian or approximately Gaussian.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…More recently, it has been shown that an analogous theory can be developed in the case where h$h$ describes (at least formally) the square root of the local time (that is, occupation field) of a Brownian trajectory; see [2, 7, 29, 30, 32]. The construction of the associated multiplicative chaos, a measure which we will denote in the following by scriptM$\mathcal {M}^{\wp }$ and which is now termed Brownian multiplicative chaos (following the terminology of [30]), is one of the first examples (together with [33] which studies random Fourier series with independent and identically distributed coefficients) of a multiplicative chaos in which the field h$h$ is not Gaussian or approximately Gaussian.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations